The experiences of remaining nurse tutors during the transformation of nursing colleges - Ellie C. van Dyk; Gisela H. van Rensburg; Juanita E. Tjallinks (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2009)
The transformation of public services and education in South Africa is part of the political and socio-economic transition to democracy. Changes are occurring in every field, including that of the health services. A qualitative study was undertaken to investigate the experiences of the remaining nurse tutors at a school of nursing during the transformation of nursing colleges and the downsizing of staff. The study on which this article is based was aimed at describing the experiences of those individuals undergoing changes in their work environment, with the purpose of contributing to recommendations regarding the ‘survival’ of transformation and the downsizing of the workplace. Three themes emerged by way of the narrative descriptions and unstructured in-depth interviews conducted during the study. The first theme, revolving around affective responses, relates to the emotions, low morale, depressive moods and anxiety caused by the transformation and downsizing. The second theme, relating to the cognitive and perceptual view of transformation, revealed the thoughts, beliefs, and opinions of the remaining nurse tutors regarding the change. The perceptions of, and opinions about how, nursing education and human dignity have been affected by this transformation were also expressed. The third theme consists of the coping responses made by the nurse tutors in the form of work-related personal and social adjustments to the transformation of the nursing colleges. The maintenance of ongoing communication and participation by the nurse tutors, as part of their counselling process, is advised. Opsomming